Characterization of sewage quality and its spatiotemporal variations in a small town in Eastern Guangdong, China - Song, Ping; Li, Yiwei; Chen, Huiru; Li, Likai; Xia, Haibo; Xiao, Yeyuan; Fang, Bingjie; Guo, Yue; Bai, Zhongrui; Ma, Lu; Wang, Jiawen; Yang, Lei; et al. (Frontiers in Water, 2024)
The domestic sewage in rural areas of South China is characterized by a relatively low concentration of organic pollutants, however, the factors causing this have not been carefully examined. This study conducted a comprehensive survey on two sewer networks in a small town of Eastern Guangdong, China, via grab water sampling at a frequency of once every 2 weeks lasting for one year. The sewage quality showed significant variations across the systems, while a gradual decrease in the concentrations of chemical oxygen demand (COD), total nitrogen (TN) and phosphorus (TP) from the upper to lower reaches of sewers could be observed. Storm events could have a flushing effect on TP in the upper reach of sewers, but a dilution effect on COD and TN in flat terrains. The diurnal pattern of sewage was largely impacted by the position of the manholes and water consumption difference between holidays and normal days. Both COD/TN and TN/TP ratios of the sewage showed a lognormal distribution dominating in the range of 2.0-3.0 and 10.0, respectively. The low ratio of COD/TN in the morning discharge peak could be attributed to the wide use of septic tanks in the area, while groundwater infiltration played more important roles in the basal flow conditions. This study could serve as a basic reference for designing and managing sewage infrastructure in rural areas of South China and highlights that prevention of groundwater infiltration is crucial to improve the efficiency of sewage infrastructure in high water table areas.